Pentingnya Komunikasi Keluarga dalam Pencegahan Kasus Kekerasan studi kasus di TK RA UMDI Ujung Lare - Rading, Astira; Tadzkirah, Tadzkirah (PT Ininnawa Paramacitra Edukasi, 2025)
Cases of violence against children are getting more and more apprehensive so that it makes parents have to be more vigilant in caring for their children. This study discusses the importance of interpersonal communication between parents and their children, especially those at an early age, to provide an understanding of how to intervene themselves. Communication is a solution in preventing sexual violence against children.In addition, communication is made so that a family can be open and harmonious with each other. Parents can provide protection to children through communication that exists between the two so that parents can equip and protect children from crimes that lurk children. The research was conducted using a literature study method with various reference sources related to the topics discussed by the author. Barriers to communication in the family can be overcome by taking time to communicate, creating openness, mutual respect and appreciation and supportive attitudes towards children.